Ethical Challenges Faced by Medical Students - Ernest Krug; Maurice Kavanagh (Association of American Medical Colleges, 2014)
Abstract Medical students face a number of ethical issues during their clinical rotations in the hospital arising from the reality that they are both at the lowest level of authority on the medical team and wish to become competent physicians. Likewise, they wish to use the knowledge they have to help others and desire good evaluations on their clinical clerkships. Thus, we created four scenarios to place a medical student in a situation where a decision must be made about how to proceed when confronted with an ethical dilemma. Four learning objectives were identified for this instructional session. We decided to pair the use of brief video vignettes with small-group discussions to highlight some key ethical principles and present strategies for dealing with ethical conundrums medical students are likely to face. We did not pursue any means for evaluating the effectiveness of this session except to note that the students appeared engaged by the use of the video vignettes. They could easily place themselves in the situation presented, comprehend the challenge, and discuss the issues raised. We believe that this type of multimedia approach is a significant contribution to teaching medical students about ethical challenges of particular importance to them as students.